Modelagem e simulação de transferência de calor em leito de partículas estacionárias sujeito a agitação intermitente - Tada, Érika Fernanda Rezendes [UNESP] (2016)
This work presents a study about heat transfer in spheres glass bed put in horizontal drum partially filled, built to solid state fermentation, using modeling and simulation tools. Two situations were analyzed: aeration above the bed surface, and absence of aeration with presence of electric resistance. During the experiments, the operation temperature was 45ºC and, when with electric resistance, the dissipated potency was maintained constant. It was collected temperature data at different positions in the bed for filling degree of 0,2 and 0,4. The proposed models were written in Matlab language and the validation occurs by comparison of simulation and experimental data. With aeration above the bed surface, the heat transfer was represented by one-phase and unidimensional model, which temperature various with radial position, with convective contour on the bed surface (h) and wall drum (hp). On surface, h was experimentally estimated and, on wall drum, hp was estimated using parametric sensibility analysis along with parameter k, with R² as response analyzed. When with electric resistance and absence of aeration, was validated a one-phase bidimensional model with temperature in function angular and radial positions. The contours employed on the wall drum and bed surface were the same as previous situation, and the presence of resistance was interpreted as a contour of constant flow. The parameters h (surface), k e hp were estimated using a parametric sensibility analysis with R² (R² ≥ 0,87). The temperature profiles obtained by simulation present good according with experimental data.